2012
DOI: 10.28945/1721
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Effective Deployment of Information Assets: An Executive Management Perspective

Abstract: In the knowledge-based economy the wealth-creating capacity of organisations is no longer based on tangible assets such as buildings, equipment, and vehicles alone. Intangible assets are key contributors to securing sustainable competitive advantage. It is therefore critically important that intangible Information Assets (IA) such as data, documents, content on web sites, and knowledge are understood and well managed. The sound management of these assets allows an organisation to run faster and better, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…IKM practices are defined as "the capability to manage information effectively over the life cycle of information use, including sensing, collecting, organising, processing, and maintaining information" (Jylhä et al, 2017: e30). Important aspects of IKM include the capability to instil and promote positive information behaviours and values in people to ensure effective use and sharing of information (Evans & Price, 2012). IKM is forecast to become the biggest growth area in health due to digital transformation of the healthcare sector (Fenton et al, 2017).…”
Section: Information and Knowledge Management In Australian Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…IKM practices are defined as "the capability to manage information effectively over the life cycle of information use, including sensing, collecting, organising, processing, and maintaining information" (Jylhä et al, 2017: e30). Important aspects of IKM include the capability to instil and promote positive information behaviours and values in people to ensure effective use and sharing of information (Evans & Price, 2012). IKM is forecast to become the biggest growth area in health due to digital transformation of the healthcare sector (Fenton et al, 2017).…”
Section: Information and Knowledge Management In Australian Hospitalsmentioning
confidence: 99%
“…Evans et al (2018: 57) found that junior doctors believe IKM is almost their entire role and that their job is "99% information gathering and 1% what decisions you make from that information". Information and knowledge are often not accessed, used and managed effectively (Evans & Price, 2012). The adverse impact of ineffective IKM is very evident in health care environments.…”
Section: Introductionmentioning
confidence: 99%
“…Private hospitals were excluded from the study. The number of hospitals included from different states and territories were as follows: Australian Capital Territory (ACT) (1); New South Wales (NSW) (33); Northern Territory (NT) (1); Queensland (QLD) (22); South Australia (SA) (12); Tasmania (TAS) (11); Victoria (VIC) (33) and Western Australia (WA) (38).…”
Section: Selecting the Research Samplementioning
confidence: 99%
“…Such a ‘knowledge focus’ relates to culture, values, and organisational structure. The organisational structure must support the organisation to deliver the right information to the right people at the right time [ 22 ]. Social norms such as openness and teamwork—where cooperation is fundamental—are key characteristics of knowledge intensive organisations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Repositioning into a data-driven organization, or at least turning the data available into a real asset [1], inevitably imposes the need to improve their quality. Indeed, organizations tend to depend on their data to make informed decisions.…”
Section: Introductionmentioning
confidence: 99%